Employment‐based abstinence reinforcement promotes opiate and cocaine abstinence in out‐of‐treatment injection drug users. Issue 4 (8th October 2014) - Holtyn, August F.; Koffarnus, Mikhail N.; DeFulio, Anthony; Sigurdsson, Sigurdur O.; Strain, Eric C.; Schwartz, Robert P.; Silverman, Kenneth
Abstract We examined the use of employment‐based abstinence reinforcement in out‐of‐treatment injection drug users, in this secondary analysis of a previously reported trial. Participants (N = 33) could work in the therapeutic workplace, a model employment‐based program for drug addiction, for 30 weeks and could earn approximately 10 per hr. During a 4‐week induction, participants only had to work to earn pay. After induction, access to the workplace was contingent on enrollment in methadone treatment. After participants met the methadone contingency for 3 weeks, they had to provide opiate‐negative urine samples to maintain maximum pay. After participants met those contingencies for 3 weeks, they had to provide opiate‐ and cocaine‐negative urine samples to maintain maximum pay. The percentage of drug‐negative urine samples remained stable until the abstinence reinforcement contingency for each drug was applied. The percentage of opiate‐ and cocaine‐negative urine samples increased abruptly and significantly after the opiate‐ and cocaine‐abstinence contingencies, respectively, were applied. These results demonstrate that the sequential administration of employment‐based abstinence reinforcement can increase opiate and cocaine abstinence among out‐of‐treatment injection drug users.